Burial history and source rocks characteristics of the montney formation, Alberta basin, Canada - Dwane, Zandile (University of the Western Cape, 2018)
Magister Scientiae - MSc (Earth Science) === More than 300 samples from the Montney Formations in the Alberta basin, offshore, Canada have been analysed with locations in various parts of the Alberta basin. These samples were mainly analyzed from two wells (well M28 & M22) to assess the organic quality, quantity as well as thermal maturation by Tmax versus PI (Production Index) from Rock-Eval Pyrolysis and Vitrinite Reflectance data. Two well locations (301 & 306) have been chosen for calibrating burial history and thermal maturation models in the Alberta basin because of their measured bottom hole temperature data which was assumed to be taken from the nearby well. These well locations also have measured Vitrinite Reflectance data which was taken directly from coal-bearing Mannville Group. The Triassic Montney Formation silty shale and shale, was deposited within an anoxic depositional environments and shows a wide variability of organic oil and gas prone Type II, II-III and III source rocks. M22 samples display excellent organic matter quantity (TOC up to 5.80%), and Type II and Type III kerogens, which are favourable for hydrocarbon generation. The high TOC values generally indicate that the condition during the deposition of sediments was favourable for organic matter production and preservation. The genetic potential (GP) and hydrogen Index (HI) is above the minimum values required for a potential source rock, suggesting that the sediments have gas and oil generating potential. However, in M22, only few samples met the requirements for the organic matter quantity, quality, and thermal maturity in order to be called source rocks. This could be because the samples from M28 were collected from outcrops which are easily affected by weathering. This significantly changed the TOC values and affected thermal maturation and Rock-eval Pyrolysis parameters.